Transmission Error Analysis and Design of Double Rollers Planetary Gear Drive with Small Tooth Number Difference - Liu Jingya; Wang Shusheng (Jixie chuandong)
A double roller type planetary gear drive with small tooth number difference is designed,and its meshing surface is composed by two array cylinder rollers,which is equidistributed in the internal gear and external planetary gear. The transmission principle and characteristic is analyzed,the determination and optimization method of the design parameters is discussed. According to its characteristic of discontinuous transmission,the transmission error is calculated and analyzed based on the error calculation formula. The research results reveal that this drive completely meets the error requirement of the power transmission and also has the possibility to be used in precision transmission with the optimal design.